1979
DOI: 10.1007/bf00234185
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological aspects of melanophores in primary culture from tadpoles of Xenopus laevis

Abstract: Melanophores from tadpoles of Xenopus laevis (Daudin) were isolated by digestion of tail fins with acetyltrypsin and collagenase and maintained in primary culture for 6 weeks up to 3 months. Within 36 to 72 h the melanophores develop one to eight dendritic processes per cell; secondary and tertiary branchings of the processes were frequently observed. The melanophores in primary culture disperse under the influence of alpha-MSH or cyclic AMP; upon rinsing out these substances the cells aggregate. In darkness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…The tail-darkening reaction was also described for tadpoles of annuran species, Agalychnis dacnicolor, Phyllomedusa trinitatus, Hyla japonica, and Rana pirica (24)(25)(26), and for a urodela, Hynobius retardatus (26). Melanophores cultured from Xenopus tadpoles at stages 50-54 also respond to light by pigment aggregation (27). The action spectrum for the photoresponse of Xenopus melanophores in intact tails was reported to have a peak at 460 nm by Lythgoe and Thompson (28), whereas Moriya et al (26) showed that a maximum response occurred at 500 nm and that the range is close to the absorption spectrum of rhodopsin in visual rod cells.…”
Section: Light Sensitivity Of Amphibian and Reptilian Chromatophoresmentioning
confidence: 80%
“…The tail-darkening reaction was also described for tadpoles of annuran species, Agalychnis dacnicolor, Phyllomedusa trinitatus, Hyla japonica, and Rana pirica (24)(25)(26), and for a urodela, Hynobius retardatus (26). Melanophores cultured from Xenopus tadpoles at stages 50-54 also respond to light by pigment aggregation (27). The action spectrum for the photoresponse of Xenopus melanophores in intact tails was reported to have a peak at 460 nm by Lythgoe and Thompson (28), whereas Moriya et al (26) showed that a maximum response occurred at 500 nm and that the range is close to the absorption spectrum of rhodopsin in visual rod cells.…”
Section: Light Sensitivity Of Amphibian and Reptilian Chromatophoresmentioning
confidence: 80%
“…Several extraocular tissues in nonmammalian vertebrates have been shown to be directly photosensitive in culture. These include the pineal gland (Deguchi, 1979), the iris (Barr and Alpern, 1963), and dermal melanophores (Seldenrijk et al, 1979). Within the past 5 years, multiple novel opsins have been identified and localized to extraocular sites in nonmammalian vertebrates.…”
mentioning
confidence: 99%
“…Seldenrijk et al (8) have reported that 90 % of cultured melanophores of Xenopus tail fin were responsive to a-MSH, whereas the light response was observed in only 40 % of the melanophores. They thought that the isolated cells more readily lost their capacity to adapt to darkness than to respond to a-MSH.…”
Section: Discussionmentioning
confidence: 99%
“…Of light sensitive chromatophores, isolated pigment cells of the sea urchin Centrostephanus longispinus displayed light sensitivity in the same manner as in normal tissue (1,12), and cultured tail fin melanophores of Xenopus laevis were also light sensitive and responded to light in the same way (8). Wakamatsu (10) found that some cultured melanophores of embryonic tissue and of young fishes of Xi phophorus maculatus exhibited a light-dependent aggregation.…”
mentioning
confidence: 99%